2022
DOI: 10.3390/ijms23062910
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses to Transglutaminase 3 in Dermatitis Herpetiformis: Lessons from Celiac Disease

Abstract: Dermatitis herpetiformis (DH) is the skin manifestation of celiac disease, presenting with a blistering rash typically on the knees, elbows, buttocks and scalp. In both DH and celiac disease, exposure to dietary gluten triggers a cascade of events resulting in the production of autoantibodies against the transglutaminase (TG) enzyme, mainly TG2 but often also TG3. The latter is considered to be the primary autoantigen in DH. The dynamics of the development of the TG2-targeted autoimmune response have been stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…[5] Due to their structural similarity and because DH usually develops as a late complication of CeD, it has been postulated that the response against TG3 could arise from an initial TG2-focused response. [16] To gain insight into the origin of TG3-specific auto-antibodies and understand their connection to the anti-TG2 response, we here characterize TG3-binding auto-antibodies in DH patients by assessing serum antibody reactivity and by generation of monoclonal antibodies (mAbs) from TG3-binding duodenal plasma cells. We demonstrate that TG3-binding antibodies are highly specific and do not show cross reactivity to TG2.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Due to their structural similarity and because DH usually develops as a late complication of CeD, it has been postulated that the response against TG3 could arise from an initial TG2-focused response. [16] To gain insight into the origin of TG3-specific auto-antibodies and understand their connection to the anti-TG2 response, we here characterize TG3-binding auto-antibodies in DH patients by assessing serum antibody reactivity and by generation of monoclonal antibodies (mAbs) from TG3-binding duodenal plasma cells. We demonstrate that TG3-binding antibodies are highly specific and do not show cross reactivity to TG2.…”
Section: Introductionmentioning
confidence: 99%
“…While a female prevalence is reported in CD, previous studies on DH showed a male to female ratio ranging from 1.1 to 1.9 ( 102 ). Epidermal transglutaminase (TG-3), rather than TG-2, is the main autoantigen in DH and it may explain why skin manifestations appear in a proportion of patients having gluten sensitive disease ( 103 , 104 ). Our group of work found a higher rate of positive antibody testing in females, confirming similar results of previous studies, while serologic testing was found to be less sensitive for male patients with CD ( 102 ).…”
Section: Dermatitis Herpetiformis: Typical and Atypical Manifestationsmentioning
confidence: 99%
“…Its function is well-described only with regard to the epidermis, where it participates in the formation of the stratified squamous epithelium [ 71 ]; for this reason, TG3 is also called epidermal TG. Anti-TG3 antibodies are commonly present in the sera of patients affected by dermatitis herpetiformis (DH), which is a cutaneous disease characterised by blistering skin and intensive itching [ 72 ]. DH is probably the most common and specific extraintestinal manifestation of CD, occurring in about 25% of CD patients.…”
Section: Tg2 In CD Pathogenesismentioning
confidence: 99%